The Efficacy of Brace Treatment for Thoracolumbar Kyphosis in Patients With Achondroplasia. Issue 16 (August 2018) - Xu, Leilei; Li, Yetian; Sheng, Fei; Xia, Chao; Qiu, Yong; Zhu, Zezhang
Abstract : Study Design: A retrospective study. Objectives: The aim of this study was to evaluate the outcome of brace treatment in the correction of thoracolumbar kyphosis (TLK) for patients with achondroplasia and to determine the factors associated with bracing efficacy. Summary of Background Data: Brace treatment has been used to correct TLK in patients with achondroplasia. However, there was a paucity of knowledge concerning its effectiveness. Methods: A total of 33 achondroplasic patients treated by bracing were included in this study. Radiographic parameters including TLK, lumbar lordosis, curve magnitude, apical vertebral translation (AVT), percentage of apical vertebral wedging, pelvic tilt (PT), and pelvic incidence were recorded for each patient at the visit. Comparison of these parameters between the initial visit and the final visit was performed using the Student t test. Factors associated with the correction of TLK were evaluated using the logistic regression analysis. Results: The mean age at presentation was 27.5 ± 13.4 months. The mean period of treatment was 32.2 ± 15.7 months, and the mean period of follow-up was 25.7 ± 11.3 months. At the initial visit, the mean value of TLK and the percentage of apical vertebral wedging were 41.7 ± 15.4° and 61.4% ± 16.2%, respectively. At the final visit, the TLK and apical vertebral wedging were remarkably reduced to 29.5 ± 20.8° and 52.1% ± 18.7%, respectively. The logistic regression analysis showed that initial TLK, AVT, percentage of apical vertebral wedging, and PT were independent factors associated with the correction of TLK. Conclusion: Brace treatment can effectively correct TLK and restore the morphology of apical vertebral body for patients with achondroplasia. Large TLK, severe apical vertebral wedging, presence of AVT, and low PT may be indicative of an unfavorable outcome, which should be taken into account at the initiation of bracing. Level of Evidence: 4